Detection and characterization of bovine hepacivirus in cattle and sheep from Hulunbuir, northeastern China - Ma, Jingge; Wei, Zhiwei; Li, Liang; Wang, Wei; Liu, Ziyan; Liu, Ning; Wei, Feng; Zheng, Xiangyu; Wang, Zedong (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundBovine hepacivirus (BovHepV) is a recently identified member of the expanding genus Hepacivirus within the family Flaviviridae. However, the genetic diversity, geographical distribution, and host range of the virus remains poorly understood.MethodsIn this study, serum samples from cattle and sheep were obtained in Hulunbuir and pooled to establish RNA libraries, which were then analyzed using transcriptome sequencing. BovHepV-positive samples were confirmed using semi-nested PCR with primers designed based on the obtained viral sequences. Comprehensive bioinformatics analyses were employed to assess sequence similarity, phylogenetic evolution, and recombination of the obtained viral strains.ResultsA total of 988 serum samples from sheep (520) and cattle (468) were collected from 12 administrative districts in Hulunbuir from June to August, 2022. Semi-nested PCR revealed 6 BovHepV-positive districts with prevalence ranging from 2.0% to 35.0% in cattle, and one BovHepV-positive district with prevalence of 2.5% in sheep. The nucleotide sequence identities between viral strains from sheep and cattle ranged from 91.3% to 93.8%, while the amino acid sequence identities were between 95.4% and 96.7%. Phylogenetic analyses classified the obtained BovHepV strains within subtype G, genotype 1. Recombination analysis revealed the intergenerational relationships among the viral strains obtained from cattle and sheep.ConclusionWe identified genetic diversity in subtype G strains in cattle and detected a BovHepV strain in a sheep for the first time in northeastern China, confirming cross-species transmission and co-circulation between cattle and sheep, thus expanding the virus’s host range.